18F-FDG PET/CT in the Diagnosis of Cervical Cancer - A. V. Leontyev; M. M. Khodzhibekova; A. I. Khalimon; M. T. Kuliev; G. F. Khamadeeva; T. L. Antonevskaya; T. N. Lazutina; A. D. Kaprin (Регуляторные исследования и экспертиза лекарственных средств)
Positron emission tomography coupled with computed tomography (PET/CT) has proven to be highly informative in the diagnosis of various malignant tumours. PET/CT examination takes into account biological and morphological data, which allow accurate tumour localisation and full staging of the disease, respectively. Cervical cancer (CC) is one of the most common, high-mortality cancers in women. The effectiveness of CC treatment depends on early diagnosis, which is connected to the assessment of local tumour spread and metastatic lymph node involvement and to the  detection of disease recurrence. The aim of the study was to  analyse the possibility of using PET/CT with 18F-FDG for the diagnosis of CC and the evaluation of treatment effectiveness. Additionally, the study aimed to analyse the potential of using other radiopharmaceuticals as biomarkers for the assessment of tumour response. Cervical malignancies are characterised by high glycolytic activity, which explains the superiority of 18F-FDG PET/CT over other traditional imaging methods in comprehensive diagnosis of patients with CC and, especially, in detecting nodal involvement and distant metastases. Also, 18F-FDG PET/CT plays an important part in the assessment of treatment effectiveness in CC patients. Further development of 18F-FDG PET/CT potential in the visualisation of malignant cervical lesions is associated with investigating the possibilities of using other specific radiopharmaceuticals to obtain information about the biological processes that support tumour cell growth: metabolism, proliferative activity, and oxygenation.